RETROSPECTIVE ASSESSMENT OF CONTROL RESULTS WITH REGARD TO COMPLETENESS AND QUALITY OF IMPLEMENTATION BY VETERINARY SERVICES OF THE SUBJECTS OF THE RUSSIAN FEDERATION OF POWERS TRANSFERRED TO THEM - M. A. Shibayev; A. S. Oganesyan; A. V. Belchikhina; K. N. Gruzdev; A. K. Karaulov (Ветеринария сегодня)
A retrospective assessment of control results with regard to completeness and quality of the implementation by state authorities of the Subjects of the Russian Federation of the powers of the Russian Federation in the field of veterinary medicine transferred to them has been carried out. It was shown that in the period from 2014 to 2016 the veterinary services of the RF subjects implemented 21,337 measures on establishment and lifting of restrictive measures/quarantine based on the occurrence of animal diseases. The study revealed that in quite a significant number of cases on establishment and lifting of restrictive measures and quarantine the veterinary services of the subjects of the Russian Federation violated the legislation of the Russian Federation. Based on the criterion “quality indicator of measures implemented by the veterinary service during the establishment/lifting of restrictive measures (quarantine) in the territory of the subject of the Russian Federation” introduced in this study, the estimated levels were determined and the quality levels of the performance of veterinary services of the subjects of the Russian Federation with regard to implementation of powers transferred to them on establishment and lifting of restrictive measures/quarantine were determined. After summarizing the results it was found that only in 37 out of 74 analyzed RF Subjects the implementation of restriction /quarantine measures was carried out at an acceptable level, and the veterinary services in 59 subjects of the country (out of 70 analyzed) showed an incompliant level of performance quality during lifting restrictions/quarantine. The retrospective analysis shows that the situation regarding quality of the implementation by government authorities of the Subjects of the Russian Federationof the powers of the Russian Federation transferred to them in the field of veterinary medicine is quite tense and causes concern. The conducted research led to understanding that the aim of the inspections should not only be assessment of compliance of the veterinary service’s activities with the regulatory acts, but systematization and analysis of violation types, as well as development and implementation of corrective measures.